EXPLORING FACTORS INFLUENCING ECONOMIC LITERACY AMONG UNIVERSITY ADMINISTRATORS IN SOUTHWESTERN NIGERIA - BAMIRO, NURUDEEN; Zakariya, Zainizam; Mohammad, Abidat Oluwashola ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2024)
Understanding economics is essential for individuals to make informed decisions and contribute to the overall well-being of the economy. This research explores the economic literacy of university administrators in southwestern Nigeria, emphasizing its importance in institutional decision-making. Data was collected from 662 academic and senior administrative staff members in fifteen universities across federal and state institutions in southwestern Nigeria using proportionate sampling techniques. The suitability of the data for the study was confirmed with a KMO value greater than 0.6. Descriptive statistics, T-tests, and ANOVA were used to analyze the dataset. The findings reveal that administrators have a solid understanding of economic concepts. No significant differences were found based on gender (t=-.972, df=660, p=.332) or university ownership (t=.996, df=660, p=.320). However, significant variations were observed according to age (F=13.780, df=661, p<0.05), job position (F=8.602, df=661, p<0.05), and academic qualifications (F=9.922, df=661, p<0.05). These differences highlight the need for targeted interventions to address knowledge gaps in specific demographic groups. The study recommends prioritizing economic literacy programs for administrators, including customized training and interdisciplinary collaboration. Future research should focus on longitudinal trends, organizational factors affecting economic